A novel FFA1 agonist, CPU025, improves glucose-lipid metabolism and alleviates fatty liver in obese-diabetic (ob/ob) mice. (March 2020) - Li, Zheng; Liu, Chunxia; Zhou, Zongtao; Hu, Lijun; Deng, Liming; Ren, Qiang; Qian, Hai
Graphical abstract: The in vitro, in vivo and modeling studies of CPU025 were explored in this study. Chronic treatment with CPU025 revealed greater benefits on glycemic control, lipid profiles and fatty liver in ob/ob mice than TAK-875, the most advanced candidate of FFA1 agonists. Highlights: CPU025 revealed dual agonistic activities on FFA1 and PPAR δ . CPU025 exhibited better glycemic control and lipid improvement than TAK-875. CPU025 improved β-cell function with dense arrangement of insulin-positive cells. CPU025 significantly reduced the vesicular steatosis and ballooning in liver. CPU025 alleviates fatty liver by multiple mechanisms. Abstract: In the effort to identify anti-diabetic drug, we discovered a novel free fatty acid receptor 1 (FFA1) agonist CPU025, which is structurally different from previously reported FFA1 agonists. The present study revealed CPU025 is a potent FFA1 agonist (EC50 = 38.7 nM) with moderate agonistic activity on PPAR δ (EC50 = 625.6 nM), and promotes insulin secretion at a glucose-dependent manner. Modeling study also illuminated CPU025 forms interaction with key residues closely related to the agonistic effects of FFA1 and PPAR δ . Long-term treatment of CPU025 exerted better glycemic control and lipid profile than TAK-875, the most advanced FFA1 partial agonist in this field. Moreover, CPU025 improved β-cell function and alleviated fatty liver in ob/ob mice. Further study suggested CPU025 could alleviate fatty liver through regulating the expression of genes involved in fatty acid β-oxidation, lipoprotein lipolysis, lipid synthesis, oxidative stress and mitochondrial function. These results indicate that long-term treatment of CPU025 improves glucose and lipid metabolism, and may be useful for the treatment of diabetes mellitus and fatty liver.